Gasification of giant sensitive plants in a fixed bed reactor - Wongsiriamnuay,T. (2015)
A giant sensitive plant (Mimosa pigra L.) is a fast growing and spreadable weed. It infests strongly along the rivers, surrounding large reservoirs, wetland reserves and agricultural fields. Its invasion threatens the production and preservation values of wetlands, and poses a major problem in agricultural areas. To avoid food-fuel dilemma, the weed may be utilized as a biorenewable energy source. In this study, it was used as feedstock for generation of producer gas. Mimosa sample were collected, and air dried. They were subsequently milled, sieved and classified into fractions of uniform particle size between 0.3 and 0.6 mm. Fuel characterization was performed using proximate and ultimate analyses. Gasification of giant sensitive plants was carried out at atmospheric pressure in a laboratory-scale fixed bed reactor to investigate the effect of reactor temperature and catalyst biomass ratio on gas yields and product gas composition. The product gas from thermochemical process was found to contain high CO and H2 which was a useful low heating value gaseous fuel. With an increase in temperature, gas yield was found to increase while char and tar were found to decrease. Increasing catalyst to biomass ratio was found to result in an increase in hydrogen, and a decrease in carbon monoxide. It appeared that the weed can be utilized as a useful renewable fuel.